A Control Design for Quad Rotor UAVs with Input Unmodeled Dynamics. Issue 11 (2015) - Krishnamurthy, Prashanth; Khorrami, Farshad
Abstract: A general six degree-of-freedom nonlinear dynamic model of a quadrotor with unknown input unmodeled dynamics is considered and a nonlinear control design is proposed for robust stabilization and trajectory tracking. The proposed controller is robust to disturbance forces and torques as well as uncertain nonlinear dynamic input perturbations. The proposed dynamic controller is based on a backstepping-based controller design for the nominal six degreeof-freedom dynamics of the quadrotor system and a scaling-based redesign of this nominal controller utilizing a dynamic scaling parameter and a dynamic state extension to address the uncertain input nonlinearities and input unmodeled dynamics.